2016
DOI: 10.1371/journal.pone.0155879
|View full text |Cite
|
Sign up to set email alerts
|

Differential Action between Schisandrin A and Schisandrin B in Eliciting an Anti-Inflammatory Action: The Depletion of Reduced Glutathione and the Induction of an Antioxidant Response

Abstract: Schisandrin A (Sch A) and schisandrin B (Sch B) are active components of Schisandrae Fructus. We compared the biochemical mechanism underlying the anti-inflammatory action of Sch A and Sch B, using cultured lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages and concanavalin (ConA)-stimulated mouse splenocytes. Pre-incubation with Sch A or Sch B produced an anti-inflammatory action in LPS-stimulated RAW264.7 cells, as evidenced by the inhibition of the pro-inflammatory c-Jun N-terminal kinases/p38 kinase/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Schisandrin A, B, and C are the main representative lignans of S. sphenanthera , many studies focus on the connections and differences between them (Leong et al, 2016; Guo et al, 2017a,b). Although Schisandrin A and Schisandrin B share the close structure, their functions and mechanism of actions had been compared and studied in various diseases (Sun et al, 2014; Guo et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Schisandrin A, B, and C are the main representative lignans of S. sphenanthera , many studies focus on the connections and differences between them (Leong et al, 2016; Guo et al, 2017a,b). Although Schisandrin A and Schisandrin B share the close structure, their functions and mechanism of actions had been compared and studied in various diseases (Sun et al, 2014; Guo et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Schisandrin A has also been reported to inhibit inflammation-induced neuronal damage by decreasing the production of NO, TNF-α and IL-6 induced by LPS in microglial cells; furthermore, various signaling pathways, including the NF-κB pathway, were indicated to be involved in this process, suggesting that schisandrin A is a promising candidate for treating inflammatory neurode-generative diseases ( 27 ). Similarly, this compound exhibited anti-inflammatory activity in LPS-stimulated RAW 264.7 cells; in particular, it increased glutathione S-transferase activity and decreased glutathione levels, thereby suppressing edema; this indicates that the anti-inflammatory action of schisandrin A is closely associated with its antioxidant effect ( 28 ). Furthermore, several previous studies have reported that lignan-like substances with a structure similar to that of schisandrin A possess anti-inflammatory activities and excellent Nrf2-induction or ROS-scavenging abilities ( 29 34 ); however, the underlying mechanisms associated with the anti-inflammatory and antioxidant activity of schisandrin A have remained to be fully elucidated.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that the most active component of SF is the lignans, which has a wide spectrum of pharmacological activities including hepatoprotective, anti-inflammatory, anti-oxidant, and anti-tumour properties [18,19,20,21]. Previous studies reported that the dibenzocyclooctadiene lignans derivatives isolated from SF, such as Schisandrin A and Schisandrin B, have potent anti-inflammatory actions via suppressing the phosphorylation of MAPKs [22]. However, as the most effective part of SF, the mechanism underlying anti-inflammatory effect of Schisandra Chinensis lignans (SCL) remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%